The Mediating Role of Callous-Unemotional Traits in the Relationship between Parental Aggression and Behavioral Problems among Chinese Preschoolers - Gengli Zhang; Yantong Zhu (MDPI AG, 2023)
It is well known that aggressive parenting is associated with behavioral problems among Western children in their early childhood, but this has rarely been examined among Chinese preschoolers. The purpose of this study is to explore the relationship between aggressive parenting, callous-unemotional traits (CU traits), and behavioral problems among a large Chinese preschool sample. Data were collected in Wuhu city, China, from 1879 preschoolers (54% of whom were male) with a mean age of 65.66 months (standard deviation = 9.41). Parents provided information about the frequency of aggressive parenting, children's behaviors, and demographic characteristics via an online questionnaire. Mediation models were applied to analyze the associations between aggressive parenting, CU traits, and behavioral problems. Preschoolers' age, gender, and family socioeconomic status were considered as covariates. The findings of our study revealed that higher frequencies of parental psychological and physical aggression were associated with high levels of CU traits, which were related to increased levels of preschoolers' behavioral problems. This study extends previous studies by revealing a positive relationship between aggressive parenting and behavioral problems among Chinese preschoolers via CU traits and highlights the risks of aggressive parenting. Interventions for improving parenting strategies and lessening callous-unemotional traits should be developed to help reduce behavioral problems.